2017
DOI: 10.2196/jmir.6931
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Design of “Lifestyle Monitoring” Technology for the Detection of Health Deterioration in Long-Term Conditions: A Qualitative Study of People Living With Heart Failure

Abstract: BackgroundHealth technologies are being developed to help people living at home manage long-term conditions. One such technology is “lifestyle monitoring” (LM), a telecare technology based on the idea that home activities may be monitored unobtrusively via sensors to give an indication of changes in health-state. However, questions remain about LM technology: how home activities change when participants experience differing health-states; and how sensors might capture clinically important changes to inform tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Manuscript types included 46 observational studies, 2, 7, 14, 2163 27 qualitative studies, 4, 64–89 12 literature reviews, 16, 17,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manuscript types included 46 observational studies, 2, 7, 14, 2163 27 qualitative studies, 4, 64–89 12 literature reviews, 16, 17,…”
Section: Resultsmentioning
confidence: 99%
“…115 Some of the 106 references related to more than one of the research questions. Twelve included references related to HF symptom perception definition, 1, 8, 17, 27, 34, 43, 54, 75, 80, 100, 102, 106 68 to description, 24, 7, 10, 16, 17, 2142, 49, 6474, 76–79, 8187, 89…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle monitoring technology for the detection of health deterioration in long-term conditions has been applied in diseases such as heart failure 88 and dementia, 89 as well as in diabetes. A 3-month follow-up study, including 1354 participants, showed that the higher the levels of patient activation and engagement with remote patient monitoring technology, the better the outcomes of glycemic control.…”
Section: Management Of Diabetes With Hyperuricemiamentioning
confidence: 99%
“…We use the terms ‘remote surveillance’ and ‘remote monitoring’ for the collection of information from the patient when she/he is not in the office/clinic or in the hospital. Others use such terms as ‘remote patient monitoring’ [174], ‘remote monitoring of patient self-care’ [175], and ‘lifestyle monitoring’ [176].…”
Section: Characteristics Of the New Systemmentioning
confidence: 99%